Applications of Microextraction Technology for the Analysis of Alcoholic Beverages Quality: Current Perspectives and Future Directions - Yue Qiu; Qi Deng; Yongqing Zhang; Baoguo Sun; Wenxian Li; Wei Dong; Xiaotao Sun (Foods)
Alcoholic beverages are loved by the majority of consumers because of their diverse characteristics and rich nutritional value; thus, ensuring their quality is necessary for maintaining the rapid development of the alcoholic beverage industry. Due to trace levels of various quality factors and the complexity of the beverage body matrix, pretreatment is usually required before analysis. Among the many pretreatment methods available, microextraction has attracted increasing attention because it aligns with the development direction of green chemistry. This review surveys advancements in microextraction techniques pertaining to three quality aspects in the most frequently consumed alcoholic beverages: baijiu and huangjiu (spirits) and wine and beer (fermented alcoholic drinks). Furthermore, new directions in their development are discussed.